Effects of chronic elevated intraocular pressure on parameters of optical coherence tomography in rhesus monkeys - Zhi-Chao Yan; Xue-Jiao Yang; Hong-Rui Chen; Shui-Feng Deng; Ying-Ting Zhu; Ye-Hong Zhuo (International Journal of Ophthalmology, 2019)
AIM: To determine the progression of parameters from optical coherence tomography (OCT) in chronic elevated intraocular pressure (IOP) monkeys. METHODS: A chronic elevated IOP model of rhesus monkeys was induced by laser photocoagulation. Representative OCT parameters, including the average and four-quadrant retinal nerve fiber layer (RNFL) thickness, and parameters from optic nerve head (ONH) analysis were collected before and after laser treatments biweekly for up to 28wk. The performance of each parameter for early progression detection was analyzed. The progressive trends toward elevated IOP were analyzed using a linear mixed-effects model. RESULTS: There were 10 successfully maintained high IOP eyes in 7 monkeys. The follow-up time was 24±5.37wk. With cumulative IOP elevation, the cup area, rim area and C/D area ratio were statistically significantly changed as early as 2wk after elevated IOP induction (P<0.05). The quadrant RNFL thickness changed at 6wk after high IOP induction, and the superior and inferior RNFL thicknesses exhibited more obvious reductions than other quadrants. The average RNFL thickness was the last one to show a significant decrease at 8wk. CONCLUSION: The parameters of ONH are most sensitive to elevated IOP in a primate glaucomatous model. These findings suggest that we should focus on those parameters instead of RNFL thickness in patients with elevated IOP, as they might present with earlier glaucomatous changes.